2020
DOI: 10.1209/0295-5075/128/54007
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic enhancement of interfacial thermal transport by mass-graded and coupling-graded materials

Abstract: With the dimension of materials shrinking into nanoscale, there has been growing interest in the Kapitza resistance which inhibits overall thermal transport. In this work, using the non-equilibrium Green's function method, we systematically investigate the optimized interfacial couplers with various gradient materials for phonon transport across one-dimensional atomic hetero-junction models. Relative to the optimized homogenous couplers, the mass-graded or coupling-graded structures are found to be applicable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
14
2
1
Order By: Relevance
“…Here, the mass interval is set as 0.15×10 -26 kg. and 8, the mass distribution with the maximum ITC is close to a nonlinear distribution, which is neither linear nor exponential distribution predicted by previous work [19,24,25] , is similar to a sinusoidal curve around linear distribution for larger thickness interlayer. In addition, the intersection point between mass distribution with maximum ITC and linear distribution is closer to the contact that has large value of atom mass.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Here, the mass interval is set as 0.15×10 -26 kg. and 8, the mass distribution with the maximum ITC is close to a nonlinear distribution, which is neither linear nor exponential distribution predicted by previous work [19,24,25] , is similar to a sinusoidal curve around linear distribution for larger thickness interlayer. In addition, the intersection point between mass distribution with maximum ITC and linear distribution is closer to the contact that has large value of atom mass.…”
Section: Resultscontrasting
confidence: 63%
“…Moreover, they found that the exponential mass distribution has better performance than the linear mass distribution in enhancing the ITC. Later, Xiong et al found that the ITC of 1D atomic junction with interlayer of both geometric graded mass and geometric graded coupling can be enhanced nearly up to 6-fold by NEGF method [25] .…”
Section: Introductionmentioning
confidence: 99%
“…For the couplers with both geometric graded mass and geometric graded coupling, the interfacial thermal conductance can be maximum enhanced nearly up to sixfold compared to the optimized homogenous case. They also found that the interfacial thermal conductance decreases with the increasing cutoff frequency ratios for all six cases due to the increasing mismatch of the cutoff frequency 53 .…”
Section: Electron-phonon Interactionmentioning
confidence: 89%
“…For the two-junction model with homogenous mass and coupling in the central part, it is found that the phonon transmission oscillates with frequency in the envelope lines of minimum and maximum transmission which can be determined by the single-junction model 51 . The interfacial thermal conductance of two-junction model for various mass-graded and coupling-graded materials was investigated by Xiong et al 53 The optimized homogenous coupler 54 , the arithmetic mass-graded and couplinggraded coupler, the geometric mass-graded and couplinggraded coupler, and the coupler with both geometric graded mass and coupling were studied. Relative to the optimized homogenous couplers, the mass-graded or coupling-graded structures were found to be applicable to improve the interfacial thermal conductance of two lead materials with both mismatched impedance and mismatched cutoff frequencies 53 .…”
Section: Electron-phonon Interactionmentioning
confidence: 99%
See 1 more Smart Citation